2013
DOI: 10.1371/journal.pone.0078218
|View full text |Cite|
|
Sign up to set email alerts
|

Catheter-Based Renal Sympathetic Denervation Significantly Inhibits Atrial Fibrillation Induced by Electrical Stimulation of the Left Stellate Ganglion and Rapid Atrial Pacing

Abstract: BackgroundSympathetic activity involves the pathogenesis of atrial fibrillation (AF). Renal sympathetic denervation (RSD) decreases sympathetic renal afferent nerve activity, leading to decreased central sympathetic drive. The aim of this study was to identify the effects of RSD on AF inducibility induced by hyper-sympathetic activity in a canine model.MethodsTo establish a hyper-sympathetic tone canine model of AF, sixteen dogs were subjected to stimulation of left stellate ganglion (LSG) and rapid atrial pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…12 During left stellate ganglion stimulation (LSGNS: 20 Hz, 2 ms) combined with atrial S 1 S 2 stimulation, the AERP and AF/AFL WOV were measured at all 4 sites. The stellate ganglion stimulation threshold is defined as the current required to produce an increase of ≥20% in systolic blood pressure or heart rate.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…12 During left stellate ganglion stimulation (LSGNS: 20 Hz, 2 ms) combined with atrial S 1 S 2 stimulation, the AERP and AF/AFL WOV were measured at all 4 sites. The stellate ganglion stimulation threshold is defined as the current required to produce an increase of ≥20% in systolic blood pressure or heart rate.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…With direct nerve activity recordings in ambulatory dogs, Tsai et al [9] observed that RDN could reduce the 24-hour average left stellate ganglion nerve activity and the paroxysmal atrial tachycardia episodes and duration. In a canine AF model with hyper-sympathetic tone induced by left stellate ganglion stimulation plus rapid atrial pacing for 3 h, RDN could almost completely prevent the increased AF inducibility, shortened atrial refractoriness, increased dispersion of atrial refractoriness, as well as elevated plasma norepinephrine [10]. In a pig model of sleep apnea, RDN resulted in an even more pronounced attenuation of atrial refractoriness shortening and AF inducibility when compared to beta-blocker treatment [11].…”
mentioning
confidence: 92%
“…Surprisingly, a recent clinical study (Symplicity HTN-3) showed the absence of beneficial effects with RDN in comparison to the sham procedure in terms of blood pressure reduction [8]. However, experimental studies [9][10][11][12][13][14] in recent years indicate that the antiarrhythmic effects of RDN may be independent of blood pressure control.Sympathetic overactivity, especially left stellate ganglion activation, has been shown to involve in the pathogenesis of AF. With direct nerve activity recordings in ambulatory dogs, Tsai et al [9] observed that RDN could reduce the 24-hour average left stellate ganglion nerve activity and the paroxysmal atrial tachycardia episodes and duration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that the treatment may have beneficial effects in other diseases (e.g. heart failure [17], chronic kidney disease [18], sleep apnea [12,19] and arrhythmia diseases [20,21]) with increased sympathetic activity. There was, however, a need for confirmation of the original observations in a larger scaled and blinded study.…”
Section: Introductionmentioning
confidence: 99%